The Development of Learning Environment Based on Learning Materials in EFL Speaking Class - Ismail, Nyak Mutia; Yoestara, Marisa (JL3T (Journal of Linguistics, Literature and Language Teaching), 2022)
Learning materials have essential roles in building learning environment—whether it becomes learner-centered, knowledge-centered, or assessment-centered. This study sought the trend of learning material development in basic speaking class. This study was qualitative in nature where the data quality was the key point measurement for further steps in finding the answer(s) to the research question. The data source was materials used for 14 meetings of Basic Conversation class. While the subject of this study was these materials, the object was the material criteria categorized based on Bransford’s et al. (2001) representation about learning material development in a classroom. The data analysis employed interactive analysis undergoing three steps which were data reduction, data display, and data verification. The results show that learner-centeredness was majorly developed in Meeting 2, Meeting 4, Meeting 5, Meeting 8, Meeting 9, and Meeting 10; knowledge-centeredness was majorly developed in Meeting 3, Meeting 6, and Meeting 7; and assessment-centeredness was majorly developed in Meeting 6 and Meeting 7. It is concluded that, first, the learning materials used for Basic Conversation class generally developed learner-centered environment as the focus was students’ interest and their background knowledge. Secondly, the materials also accentuated on knowledge-centeredness, though not as much as the first result. Last, there was also slight but still substantial development of assessment-centered environment. It implies that there can be found ample balance between these three types of learning centeredness to promote good learning environment.